2010
DOI: 10.1055/s-0030-1250354
|View full text |Cite
|
Sign up to set email alerts
|

In vitroAntimicrobial Activity of Brazilian Medicinal Plant Extracts against Pathogenic Microorganisms of Interest to Dentistry

Abstract: This study evaluated the susceptibility of oral pathogenic microorganisms Candida albicans, Streptococcus mutans, Staphylococcus aureus, and Aggregatibacter actinomycetemcomitans to Brazilian medicinal plant extracts of Schinus terebinthifolius (aroeira), Croton campestris (velame), Lafoensia pacari (pacari), Centaurium erythraea (centáurea), Stryphnodendron adstringens (barbatimão), and Anacardium humile (cajuzinho-docerrado), as compared to standardized antimicrobial agents (nystatin, chloramphenicol and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 10 publications
2
42
0
2
Order By: Relevance
“…Both articles reported the use of dimetylsulfoxide as solvent to solubilize the powdered extracts. Thus, although both hexanic extracts were active at higher than clinically acceptable concentrations, the results published by Ohara et al (2008) and Pereira et al (2011) suggested that solvent such as dimetylsulfoxide can help some molecules to diffuse into agar medium and make possible the use of agar diffusion technique for apolar substances as suggested by Valgas et al (2007).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Both articles reported the use of dimetylsulfoxide as solvent to solubilize the powdered extracts. Thus, although both hexanic extracts were active at higher than clinically acceptable concentrations, the results published by Ohara et al (2008) and Pereira et al (2011) suggested that solvent such as dimetylsulfoxide can help some molecules to diffuse into agar medium and make possible the use of agar diffusion technique for apolar substances as suggested by Valgas et al (2007).…”
Section: Resultsmentioning
confidence: 95%
“…In this review the most frequent category used was polar solvent but it is worth noting that a combination of solvent or crude extracts obtained directly from the plant without solvent addition was also described. By agar diffusion technique, from non-polar solvent extraction, only two showed  18 mm inhibition zone: The hexanic extract from bark of Cinamonum verum (OHara et al, 2008) and the hexanic extract from bark/leaves of Schinuster ebinthifolius (Pereira et al, 2011). Both articles reported the use of dimetylsulfoxide as solvent to solubilize the powdered extracts.…”
Section: Resultsmentioning
confidence: 99%
“…With this perspective, studies on medicinal plants have been targeting the discovery of new chemical molecules able to overcome the shortcomings of synthetic agents currently used in medicine and dentistry. [15][16][17][18] In this bioprospection study, we evaluated the antimicrobial activity of hydroalcoholic extracts of B. forficata and C. quercifolius against microorganisms of clinical relevance, particularly in oral candidiasis, and their antiproliferative potential against six tumor cell lines and keratinocytes.…”
Section: 5005/jp-journals-10024-2098mentioning
confidence: 99%
“…This plant has used in traditional medicine as antipyretic, analgesic and in the treatment of urogenital diseases . Several studies have shown that S. terebinthifolius produce pharmacologically important substances, such as anticancer (Bendaoud et al, 2010;Matsuo et al, 2011), antimicrobial (Silva et al, 2010;Pereira et al, 2011), antioxidant (Bendaoud et al, 2010), healing purposes (Estevão et al, 2013) and antiproliferative (Queires et al, 2013).…”
Section: Introductionmentioning
confidence: 99%